KARAKTERISTIK WOOD PELLET DARI LIMBAH KAYU KARET (Hevea brazilliensis Muell. Arg) SEBAGAI ALTERNATIF SUMBER ENERGI TERBARUKAN - Ari Adrian; Rudianda Sulaeman; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research to investigate the characteristics of wood pellets from wood rubber waste as  alternative renewable energy sources and determine the best treatment. This research was conducted in experiments with completely randomized design (CRD), which consists of three treatments three replications, with the use of wood rubber waste, tapioca flour and water as well as the tools use are peletmill, calory meter combustion bomb, hammermill, oven, container, stirrer, weigher, measure cups, stopwach, wood pellets stove and camera. It can be concluded that the water content wood pellet 15,06% - 17,26%, wood pellet density 0,408 g/cm3 (408 kg/m3) – 0,628 g/cm3 (628 kg/m3), long burn wood pellets 5,42 minutes/200gr – 7,29 minutes/200gr and a calorific value  4029 Kcal/kg - 4106 Kcal/kg. Treatment to three with tapioca powder rubber wood + 30% + 300 ml water have the appropriate or best treatment approach by SNI, where the water content of 15,06%, density of 0,628 g/cm3 (628 kg/m3), long burning 5,42 minutes/200gr and calorific value of 4106 Kcal/kg. Keywords: waste, rubber wood, wood pellets, energy